Consequences of endometriosis in the menopause - Szubert, Maria; Suzin, Jacek; Kowalczyk-Amico, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2012)
Endometriosis can affect between 2% and 5% of postmenopausal women. The disease can occur de novo or develop from residual endometriosis. The history of endometriosis can affect the quality of postmenopausal life because of its consequences. Pelvic pain can be a symptom of adhesions caused by endometriosis. The use of hormone therapy may influence the disease recurrence. A serious consequence of endometriosis in the menopause is a possibility of malignant transformation of the lesions. This review summarizes the pathogenic mechanisms that underlie maintaining or development of endometriotic lesions in the hypoestrogenic environment after menopause. We present also the newest data about molecular changes leading from benign endometriotic lesions to atypia and cancer.